Regulatory T cell therapy in lung transplantation: bridging the gap from bench to bedside - Li, Qianwei; Li, Guorui; Feng, Jinteng; Zhang, Guangjian (Frontiers in Immunology, 2025)
Lung transplant recipients face significantly poorer outcomes compared to other solid organ transplants, with median survival rates substantially lower despite current immunosuppressive regimens. Regulatory T cell (Treg) therapy has emerged as a promising approach for immune modulation, though its successful application in lung transplantation requires understanding of the unique pulmonary immune environment. This review examines how Tregs mediate immune responses in lung allografts and their role in rejection and tolerance pathways. We evaluate emerging evidence from preclinical studies of Treg therapy in lung transplantation, complemented by clinical experience from kidney and liver transplant trials that demonstrate safety and potential for reducing conventional immunosuppression. The analysis addresses key considerations for clinical implementation, including therapeutic strategies, timing of administration, and integration with existing protocols. This framework aims to guide the development of Treg-based therapies specifically tailored for lung transplant recipients.